Développer et reduire:
A=4x(3x-1)-2x²(2x+3)
B=(5x-2)(3x-1)+4x(x-6)
C=(2x-3)²
D=(5x-6)(5x+6)
E=(x+7)²-(9x-4)(-3x-1)

PS: X= la lettre x

1
A = 12x^2 - 4x - 4x^3 - 6x^2 = -4x^3 + 6x^2 - 4x = -x (4x^2 - 6x + 4)
B = 15x^2 - 5x - 6x + 2 + 4x^2 - 24x = 19x^2 - 34x + 2
C = 4x^2 - 12x + 9
D = (5x)^2 - 6^2 = 25x^2 - 36
E = x^2 + 14x + 49 + 27x^2 + 9x - 12x - 4 = 28x^2 + 11x + 45

Réponses

2013-12-10T23:20:17+01:00
Bonsoir,

A = 4x(3x - 1) - 2x²(2x + 3)
A = 12x² - 4x - 4x^3 - 6x²
A = -4x^3 + 6x² - 4x

B = (5x - 2)(3x - 1) + 4x(x - 6)
B = 15x² - 5x - 6x + 2 + 4x² - 24x
B = 19x² - 35x + 2


C = (2x - 3)²
C = (2x)² - 2*(2x)*3 + 3²       (formule : (a - b)& = a² - 2ab + b²)
C = 4x² - 12x + 9

D = (5x - 6)(5x + 6)     (formule : (a - b)(a + b) = a² - b²)
D = (5x)² - 6²
D = 25x² - 36

E = (x + 7)² - (9x - 4)(-3x - 1)
E = x² + 14x + 49 - (-27x² - 9x + 12x + 4)
E = x² + 14x + 49 + 27x² + 9x - 12x - 4
E = 28x² + 11x + 45